Orientasi Pendidikan Islam Pada Perguruan Tinggi Berbasis Pesantren Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta (STITMA) - Achmad Fadhel Fikri; Hilalludin Hilalludin; Azfa Nabil Shafi (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the role of Islamic education at Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, an institution based on pesantren principles integrating formal education with traditional pesantren values. Through a literature review method, the study explores the fostering of Islamic scholarship, the formation of Islamic leadership, Islamic academic environment, and community service at the university. Findings highlight a strong commitment to producing graduates who excel academically while embodying noble character and commitment to Islamic values. The implications underscore the importance of integrating Islamic values into higher education curricula to cultivate a high-quality, globally competitive generation.